2007
DOI: 10.1017/s0305000907008124
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between parental reports of infants' receptive vocabulary and infants' behaviour in a preferential looking task

Abstract: Two experiments are described which explore the relationship between parental reports of infants' receptive vocabularies at 1 ; 6 (Experiment 1a) or 1 ; 3, 1 ; 6 and 1 ; 9 (Experiment 1b) and the comprehension infants demonstrated in a preferential looking task. The instrument used was the Oxford CDI, a British English adaptation of the MacArthur-Bates CDI (Words & Gestures). Infants were shown pairs of images of familiar objects, either both name-known or both name-unknown according to their parent's resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 34 publications
8
114
1
Order By: Relevance
“…Indeed, this supposition is consistent with false negatives in parents' MCDI reports of their infants' comprehension repertoires as compared with subsequent preferential looking measures of these infants' word learning conducted in the laboratory (Houston-Price, Mather, & Sakkalou, 2007).…”
Section: Preferential Looking Versus Preferential Reaching: Implicatisupporting
confidence: 67%
“…Indeed, this supposition is consistent with false negatives in parents' MCDI reports of their infants' comprehension repertoires as compared with subsequent preferential looking measures of these infants' word learning conducted in the laboratory (Houston-Price, Mather, & Sakkalou, 2007).…”
Section: Preferential Looking Versus Preferential Reaching: Implicatisupporting
confidence: 67%
“…Parental vocabulary reports support this interpretation, with very low levels of reported comprehension for all six familiar object names. However, a study by Houston-Price, Mather, and Sakkalou (2007) found that British parents appear to underestimate comprehension vocabulary for infants between 15 and 21 months of age. It is currently unknown whether parents underreport vocabulary for younger infants.…”
Section: Discussionmentioning
confidence: 98%
“…As noted above, parental report may overestimate or underestimate toddler knowledge (e.g., Houston-Price et al, 2007;Tomasello & Mervis, 1994). Nevertheless, in a final analysis we considered the toddlers' performance on the colour related distractor trials in the light of the parental reports of their knowledge and use of colour labels.…”
Section: Codingmentioning
confidence: 99%